Thymol and carvacrol strongly inhibit biofilm formation and growth of carbapenemase-producing Gram negative bacilli - Raei, P.; Pourlak, T.; Memar, M. Y.; Alizadeh, N.; Aghamali, M.; Zeinalzadeh, E.; Asgharzadeh, M.; Kafil, H. S. (Cellular and Molecular Biology, 2017)
Discovery of novel drugs with new mechanisms of action and without cross-reaction with current therapeutic agents is crucial in the management of infections caused by multi-drug resistant (MDR) bacteria. The aim of the present study was to investigate effects of carvacrol and thymol on biofilm formation and antimicrobial activity against different carbapenemase-producing Gram negative bacilli. The antimicrobial and antibiofilm effect of thymol and carvacrol was investigated against strains harboring different genes related to carbapenemase resistance. Antimicrobial resistance was examined by an agar dilution method and antibiofilm effect was evaluated by microtiter plate assay and staining by crystal violet. Thymol and carvacrol had antibacterial effects ranging from 200-1600 Î¼g/mL and 62-250 Î¼g/mL respectively, and antibiofilm effect from 125-500 and 400-1600 Î¼g/mL respectively. Seoul imipenemase- (SIM) producing isolates had the highest sensitivity, and NDM (New Delhi metallo-beta-lactamase) producing isolates had the lowest sensitivity to these components. Findings of the present study indicated a potential role of carvacrol and thymol in controlling carbapenemase-producing gram negative bacterial infections. These findings helped to develop herbal drugs for replacing antibiotics. In addition, their antibiofilm effects showed that carvacrol and thymol inhibit biofilm formation of carbapenemase-producing strains.